2008
DOI: 10.1002/anie.200803549
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Noise Stemless PNA Beacons for Sensitive DNA and RNA Detection

Abstract: A change of the energy transfer mechanism (from contact quenching to FRET) increases the responsiveness of fluorescent hybridization probes. The communication between a responsive fluorescent base surrogate (see picture, green) and a near‐infrared dye (red) in peptide nucleic acid provides probes that are extremely dark in the single strand. Hybridization furnishes strong fluorescence increase with a 200 nm shift in emission maximum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 40 publications
1
69
0
Order By: Relevance
“…An extended applicability to sequence contexts has been reported for the dual-labeled TO-containing stem-less PNA beacons. 36 Whether such probes enable live cell RNA imaging remains to be evaluated. The use of differently colored PNA FIT-probes in this feasibility study revealed significant differences in the expression pattern of influenza H1N1 mRNAs coding for neuraminidase (NA) or matrix protein 1 (M1).…”
Section: ■ Discussionmentioning
confidence: 99%
“…An extended applicability to sequence contexts has been reported for the dual-labeled TO-containing stem-less PNA beacons. 36 Whether such probes enable live cell RNA imaging remains to be evaluated. The use of differently colored PNA FIT-probes in this feasibility study revealed significant differences in the expression pattern of influenza H1N1 mRNAs coding for neuraminidase (NA) or matrix protein 1 (M1).…”
Section: ■ Discussionmentioning
confidence: 99%
“…The stemless PNA beacon was also used to detect the TAR loop from the HIV genome within an in vitro transcribed 650-nucleotide long TAR-CAT fusion, and up to 24-fold increase in signal was found. [95] Seitz also used PNA based hairpin peptide beacons in which the specific loop region was recognised by a protein target, which opens the hairpin structure increasing the fluorescence. Two targets were chosen: Src kinase and aspartic acid protease, rennin, which showed an 8-11-fold increase in fluorescence for the target proteins; this demonstrates the possibility for the use of hairpin peptide beacons in the detection of a broad range of proteins ( Figure 5).…”
Section: Bioanalytical and Diagnostic Applicationsmentioning
confidence: 99%
“…Assignment of the H7, H8, H11, and H12 protons of U MBF were confirmed by the 2D DQF-COSY and NOESY spectra. Assignments of H2 protons of adenine and of H6, H8, and H1' protons of canonical deoxynucleotides and H7, H8, H11, and H12 proton of U MBF were confirmed by the 1 H, 13 C HSQC spectrum. Assignments of the methyl group of thymine and H2' and H2'' protons of deoxynucleotides were confirmed by the 2D TOCSY and NOESY spectra.…”
Section: Methodsmentioning
confidence: 80%